Smartroof system - Ibrahim, Nur Izzatiey Nadia (2022)
The Green Campus concept is an innovation to existing elements such as improving the concrete ratio or producing new products. High technology has contributed to the improvement of the country's economy in construction industry. As know, clay roof tiles are frequently used on buildings including homes, schools, and hostels. In addition to environmental pollution, utilizing clay roof tiles will also have a harmful effect on individuals and building structures. In attempt to develop the Green Campus Concept in this century, clay tiles should be taken into consideration in construction. This is due to the fact that clay tile installation and repair require specialised labour and take some time to complete. To portray the idea of a green campus, this research used the analytical techniques of observation, simulation, and literature review. The problems that occur can be addressed with the innovative product produced which is Smartroof System. This product is compatible with the Green Concept, particularly in student accommodation.